Effect of Supplementation of Area Specific Mineral Mixture on Performance of Crossbred Cows with Reproductive Disorders in Kakatpur Block - Satapathy, Debasish; Mishra, S.K.; Swain, R.K.; Sethy, Kamdev; Sahoo, Gyana Ranjan (Indian Journal of Animal Nutrition, 2018)
The experiment was conducted to evaluate the effect of area specific mineral mixture on growth performance, blood parameters and reproductive efficiency in crossbred cows in Kakatpur block of Odisha. Forty crossbred animals were selected for the experiment and divided in to two equal groups. Among themnumber of anestrus animals and repeat breeder animals were 14 and 26, respectively. Therefore, each group had 7 anestrus and 13 repeat breeder animals. The animals in control group (T1) were fed as per farmers’ practicewhile in groupT2, the animals were supplemented with area specific mineral mixture @ 50 g/d/animal for a period of 60 days. After the experiment, higher (P